A social history of rice in Turkey - Ceylan, Okan. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2020., 2020)
This dissertation examines the transformation of rice farming before the state, the society, and the economy in Turkey between 1948 and 2018. Rice is one of the most important fields of application of the Green Revolution after the Marshall Plan is examined from a spatial point of view in three basins such as the Meriç Basin, the Lower Kızılırmak-Lower Yeşilırmak Basins and Karacadağ Agricultural Basin. Both the geographical locations of these basins in Turkey and the differences in their agricultural structures and human capital are determinative in their preference as a field study. However, apart from these basins, there has been rice farming culture in South Marmara, Adana, West and Central Black Sea sub regions. In other words, this dissertation both explains the story of agricultural transformation in a historical process and presents a comparative perspective among these basins on a spatial scale. Therefore, this study can be evaluated in the fields of economic history, social history and environmental history. The main claim of this dissertation is to prove that thanks to the biological and agricultural properties of rice, it is a historical actor that directs the state, society, and the economy. On this basis, this study is far from putting sharp boundaries between nature and society and the anthropocentric historiography. In this context, this study examines the subject by putting the reciprocal relations and interests between the desires of human beings and the biological and agricultural requirement of rice into the center. The main purpose of this study is to explain the bureaucratic, economic and social networks of rice from its cultivation and harvest to its processing in to paddy and consumption. The main findings of this dissertation are that rice is a social, cultural, economic, artistic and bureaucratic commodity. In this context, rice requires specialized and intensive labor to collaborate with society, the state and market actors to be able to spread and carry its genes into the future. Besides, acquisition, nutrition and profit underlie in the desire of a human being toward rice. To sum up rice with one word, it can be conceptualized as the crop of controversies. As a matter of fact, it is too difficult to find any other crop that accommodates collaboration and conflict of interest and also the bureaucratic control in the cultivation of rice and free market economy in the sale of rice at the same time.
Keywords: Rice seed industry -- Turkey.